Penerapan Pemasaran Digital pada UMKM “Warung Sate Aira” Kabupaten Bengkalis - Wina Wiranda; Rizqa Arimurti; Erma Domos; Rini Arvika Sari (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
This community service project aims to implement a digital marketing strategy for the micro, small, and medium enterprise (MSMEs) Warung Sate Aira in Bengkalis using a qualitative descriptive approach through observation, interviews, and documentation. A SWOT analysis was conducted to identify the strengths, weaknesses, opportunities, and threats in business development. The results revealed that the main strengths include a distinctive flavor, strategic location, and loyal customers, while the challenges involve intense competition, high operational costs, and limited digital promotion. Based on the STP (segmenting, targeting, positioning) approach, the business targets culinary enthusiasts and positions itself as a provider of high-quality warm chicken satay. The marketing mix strategy includes improving product quality, offering affordable prices, utilizing strategic locations, and using digital platforms such as Instagram and Maxim, supported by both direct and online promotions. The implementation of this strategy led to increased business visibility, customer interest, and brand awareness. Moreover, this activity provided the business owner with a better understanding of digital marketing and developed more practical, efficient, and sustainable promotional strategies for MSME growth in the digital era.